2009
DOI: 10.1007/s00296-009-1053-x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and leptin serum concentrations in patients with rheumatoid arthritis

Abstract: International audienceAdipose tissue is regarded as an active metabolic and endocrine organ producing adipokines. The purpose of the study was to evaluate adiponectin and leptin concentrations in rheumatoid arthritis (RA) patients (pts) in relation to disease duration and activity. The study group consisted of 80 RA pts. Serum adiponectin and leptin concentrations remained within normal ranges. Adiponectin concentration correlated positively both with the age and disease duration. Both adipokines levels correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 37 publications
(46 reference statements)
3
45
0
Order By: Relevance
“…Regarding the association of leptin with RA duration and activity, results are also inconclusive. Leptin level was demonstrated to be independent of RA activity or duration in different studies [8, 12, 13, 32]. But, there are also other studies in which, serum leptin was correlated to RA activity and/or duration [2, 4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the association of leptin with RA duration and activity, results are also inconclusive. Leptin level was demonstrated to be independent of RA activity or duration in different studies [8, 12, 13, 32]. But, there are also other studies in which, serum leptin was correlated to RA activity and/or duration [2, 4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is proinflammatory adipokine involved in different inflammatory diseases such as rheumatoid arthritis 29. It is produced mainly by fat tissue and is always correlated with BMI and TNF-α and is also higher in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Some, but not all, studies have found altered circulating levels of adipokines in patients with RA, and associations of adipokine levels with disease activity and with antiTNF treatment have been inconsistent. [60][61][62] Further research is required to elucidate the complex relationship between insulin r esistance, a dipokines and inflammation in RA.…”
Section: Diabetes and Insulin Resistancementioning
confidence: 99%